Instilling the integrity of human values in the elementary school curriculum: a global perspective review - Egha Devika Sirait; Elisa Rahma Putri; Eghy Jesika Sirait; Roma Ananda Manalu; Elfrianto Elfrianto (Holistic Science, 2025)
The integrity of human values ??is the main foundation in the character formation of elementary school students amidst the increasingly complex currents of globalization. Global developments present universal values ??such as justice, empathy, tolerance, peace, and respect for human dignity that need to be instilled from an early age. Elementary schools have a strategic role in internalizing these values ??through a systematic curriculum with a global perspective. This article aims to examine the instillation of the integrity of human values ??in the elementary school curriculum from a global perspective. The research method used is a literature study by analyzing national and international scientific journals, educational policy documents, and reports from global organizations relevant to character education and global citizenship. The results of the study indicate that the integration of human values ??can be achieved through values-based learning, character education, and the development of a contextual and inclusive curriculum. The global perspective emphasizes the importance of developing global citizenship competencies, such as cross-cultural empathy, respect for diversity, and concern for global humanitarian issues. Teachers play a crucial role as moral role models and learning facilitators in instilling human values ??through role models, habituation, and critical reflection in the learning process.